2022
DOI: 10.1590/fst.54622
|View full text |Cite
|
Sign up to set email alerts
|

Combination of machine learning and intelligent sensors in real-time quality control of alcoholic beverages

Abstract: Machine learning (ML) featured on its ability of learning and extracting features from a large set of data and automatically building statistical models. Through cooperation with intelligent sensors, which is designed to imitate human organs to analyze the sensory characteristics of foods, ML-based intelligent sensory systems such as electronic nose (E-nose) and electronic tongue (E-tongue) are developed for sensing applications in food industry. Consumption of alcohol beverages keep growing worldwide in recen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The results are shown in Figure 3D. All the 60 repeated qualitative PCR experiments yielded targeted amplification products, thus meeting the requirements for determining the qualitative detection limit of gene editing components [27]. Therefore, the detection limit of the method was taken as 0.1%.…”
Section: Sensitivity Analysis Of the Qualitative Pcr Methodsmentioning
confidence: 76%
“…The results are shown in Figure 3D. All the 60 repeated qualitative PCR experiments yielded targeted amplification products, thus meeting the requirements for determining the qualitative detection limit of gene editing components [27]. Therefore, the detection limit of the method was taken as 0.1%.…”
Section: Sensitivity Analysis Of the Qualitative Pcr Methodsmentioning
confidence: 76%
“…support vector machine (SVM), showed that the employed set of MOS gas detectors accurately identified pesticide residues in apple samples [193]. Gas detection is also essential in the production of various food products like coffee [194], beer [172], cheese [195], and wine [170,196], as well as baking processes [197], in which monitoring the presence of various gases allows the assessment of correctness of production processes and product quality. Experimental results show that the developed E-nose system using SnO2-based MOS gas sensors combined with six machine learning techniques (decision tree, random forest, XGBoost, SVM, convolutional neural network (CNN), and CNN+LSTM) achieves good performance in coffee aroma recognition [194].…”
Section: Application Of Mos Gas Sensors In the Food Industrymentioning
confidence: 99%
“…LSG was applied to make up glucose biofuel cells, and the electrode was integrated with active catalytic nanomaterials to take advantage of the biochemical energy of glucose [17]. Applying a non-thermal laser scribe method on graphene oxide (GO)/silver nanowires (SNWs) thin film reduced it to rGO/SNW, resulting in 80% transparency and 70 Ω cm −1 sheet resistance that could be used as an optoelectronic device [18]. When Cu x O nanoparticle were immobilized on LSG a highly efficient and inexpensive electrocatalyst for hydrogen production resulted [19].…”
Section: Introductionmentioning
confidence: 99%
“…By coupling LSG electrochemical sensors to machine learning (ML) models, it is possible to achieve rapid data acquisition, and the intelligent and automated analysis of large amounts of data, with accurate results [18,19]. The association of mathematical and statistical methods to analyze, process, and extract crucial information from large complex datasets can be fundamental in complex cases [20].…”
Section: Introductionmentioning
confidence: 99%